Miristhma boyi sp. n. (Hymenoptera: Pteromalidae: Pteromalini), a new species from Uruguay - Perioto, Nelson W.; Lara, Rogéria I. R. (Entomological Communications, 2024)
This study is focused on the parasitic wasps Miristhma Bouček, 1993 (Hymenoptera: Pteromalidae: Pteromalinae: Pteromalini), a small and poorly represented genus in entomological collections. Herein Miristhma boyi sp. n. Perioto & Lara is described as new to science based on specimens obtained from eastern Uruguay. Additionally, we provide illustrations, an identification key for these species, and a map with the geographical distribution of the known species of Miristhma based on the new record and literature data.